Feebly θ-closed sets and its properties (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The main goal of this paper is to introduce the concept of feebly θ-open set and investigates the properties of feebly θ-interior, feebly θ-closure, feebly θ-exterior, feebly θ-frontier of a set.